Perceptions of traditional health practitioners on violence in the Helderberg Municipal Area, Western Cape - Diana Gibson (AOSIS, 2013)
This study on perceptions of violence was conducted with 56 traditional health practitioners (diviners: amagrirha) in the Helderberg Municipal Area of Cape Town Metro. It forms a subsection of a larger study on African medicine. This particular research focuses on how traditional health practitioners perceive violence, including gender-related violence. Individual, in-depth interviews were done with 21 traditional health practitioners and focus group discussions were held with 35 participants. The paper reports on their understanding of, as well as the meanings attached to, community and gender-based violence in an urban setting. The traditional health practitioners related violence to a range of disconnections in society, ranging from not adhering to traditional norms and practices, to breaks in relations between parents and children, within families and in marital- and sexual relations. They referred to a general sense of disjuncture between the living and the ancestral worlds. The accumulative effect of this sense of not being connected was seen as damaging and a precursor to violence. In two sites where there were high concentrations of violence, ceremonies were held to purify the areas by ritual. In addition to attending to the physical manifestations of illness, distress and violence, these traditional health practitioners attempted to enhance and restore proper social relationships between the living, as well as between the living and the dead.